Questioning method in the human geographical research (on the example of the poll of Kharkiv`s residents about city administrative districts) - Mazurova, Anastasiia (Human Geography Journal, 2017)
For the city of Kharkiv as the second for population city of Ukraine, determination of a thought of citizen’s about industrial, residential, landscape and recreational zones, social and cultural infrastructure, specialization and accommodation comfort is very important. Through the collection and analysis of such information may determine the main problems plaguing citizen and the most optimal ways to solve them, because usually exactly citizens can see practical and effective methods of problem solving to optimize urban space.The aim of this study was to determine the attitude and awareness of citizens of Kharkiv`s administrative districts on industrial, residential, landscape and recreational, cultural infrastructure, specialization by the method of questioning. It was also considered accommodation comfort, the most popular objects of landscape and recreational, cultural spheres.The most comfortable districts for living are Nemyshlyansky, Kievsky and Shevchenkivsky districts. The average level of living comfort is in Moskovsky, Osnovyansky and Slobidsky districts. Uncomfortable districts by residents are Industrial, Novobavarsky and Kholodnohorsky districts. The detailed analysis of conditions of accommodation of the population in areas with low comfort and identifications of ways of improvement is required.In general, we note that using the questioning method was identified a number of administrative areas of the city that need developing additional programs to improve their infrastructure and living conditions. However it is necessary to consider that only complex optimization of all city territory is possible, considering features of each administrative-territorial district of the city and communications between them.